Safety and risk of febrile recurrence after early antibiotic discontinuation in high-risk neutropenic patients with haematological malignancies: a multicentre observational study. (24th June 2022) - Paret, Raphael; Le Bourgeois, Amandine; Guillerm, Gaëlle; Tessoulin, Benoit; Rezig, Schéhérazade; Gastinne, Thomas; Couturier, Marie Anne; Boutoille, David; Lecomte, Raphael; Ader, Florence; Le Gouill, Steven; Ansart, Séverine; et al.
Abstract: Background: Early antibiotic discontinuation according to the Fourth European Conference on Infections in Leukaemia (ECIL-4) recommendations is not systematically applied in high-risk neutropenic patients with haematological malignancies. Methods: A retrospective multicentre observational study was conducted over 2 years to evaluate the safety of early antibiotic discontinuation for fever of unknown origin (FUO) during neutropenia after induction chemotherapy or HSCT, in comparison with a historical cohort. We used Cox proportional hazards models, censored on neutropenia resolution, to analyse factors associated with febrile recurrence. Results: Among 147 included patients in the ECIL-4 cohort, mainly diagnosed with acute leukaemia ( n  = 104, 71%), antibiotics were discontinued during 170 post-chemotherapy neutropenic episodes. In comparison with the historical cohort of 178 episodes of neutropenia without antibiotic discontinuation, no significant differences were observed regarding febrile recurrences [71.2% (121/170) versus 71.3% (127/178), P =  0.97], admission in ICUs [6.5% (11/170) versus 11.2% (20/178), P =  0.17], septic shock [0.6% (1/170) versus 3.9% (7/178), P =  0.07] and 30 day mortality [1.4% (2/147) versus 2.7% (4/150), P =  0.084]. In the ECIL-4 cohort, the rate of bacteraemia in case of febrile recurrence was higher [27.1% (46/170) versus 11.8% (21/178), P <  0.01] and antibiotic consumption was significantly lower (15.5 versus 19.9 days, P <  0.001). After early antibiotic discontinuation according to ECIL-4 recommendations, enterocolitis was associated with febrile recurrence [HR = 2.31 (95% CI = 1.4–3.8), P <  0.001] and stage III–IV oral mucositis with bacteraemia [HR = 2.26 (95% CI = 1.22–4.2), P =  0.01]. Conclusions: After an FUO episode in high-risk neutropenia, compliance with ECIL-4 recommendations for early antibiotic discontinuation appears to be safe and mucosal damage was associated with febrile recurrence and bacteraemia. Prospective interventional studies are warranted to assess this strategy in high-risk neutropenic patients.